ANALISIS SPASIAL KETERJANGKAUAN RETAILER ROKOK TERHADAP PERILAKU MEROKOK PADA SISWA SEKOLAH MENENGAH ATAS (SMA) DI KEC. WANGI-WANGI DAN WANGIWANGI SELATAN KABUPATEN WAKATOBI - Muhammad Ihsan Awaluddin; Supriyati; Anis Fuad (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2020)
Background: Indonesia is still the third country with the most active smokers in the world (61.4 million smokers), after China and India. Data on cases of smoking violations at school in 2017 were 64 cases of smoking violations in all high schools in Wangi-Wangi District and 45 cases in high schools in Wangi-Wangi Selatan District and until August 2018 there were 68 reported cases of smoking violations in high school in these 2 subdistricts and is predicted to continue to increase. Objective: To analyze the spatial relationship between the afford ability of cigarette retailers by high school students on smoking behavior spatially in Wangi-wangi District and South Wangi-wangi District, Wakatobi Regency. Methods: Type of research is an analytic survey, using a cross sectional study design with consecutive sampling technique. Where the sample is high school students with a sample of 94 people. Results: The results showed that there was a significant correlation between the affordability of retailers (p-Value = 0.048) with the smoking behavior of high school students PR 2.09 (95% CI 0.015-4.123), and the smoking behavior of friends (p-Value = 0.010) with the smoking behavior of high school students PR 1.82 (95% CI 1,096-13,662), GeoDa spatial regression test shows that retailer’s affordability (p = 0.00922), friend’s smoking behavior (p = 0.00204) and parental smoking behavior (p = 0.03181) shows spatial relation ship with smoking behavior, where the parental smoking behavior variable has weak spatial autocorrelation because its Morran’s index is close to zero. Conclusion: There is a spatial relationship between the affordability of retailers, friend smoking behavior and smoking behavior of parents with smoking habits of high school students in Wangi-Wangi District and WangiWangi South District, Wakatobi Regency